(untitled) (Research, Society and Development, 2024)
Poisoning is defined as an adverse event resulting from the action of chemical substances that induces a pathology in an individual. The World Health Organization (WHO) has reported three million hospital admissions occurring annually due to toxic exposure worldwide. The growth of SARS-CoV-2 infection cases in 2020 also significantly increased calls to Poison Centers due to exposure to cleaning products, hand sanitizers, and disinfectants in early March 2020 in the United States. Based on this scenario, it was hypothesized that the pattern of exogenous intoxication has changed. Therefore, the aim of this study was to analyze the epidemiological profile of exogenous intoxications recorded by CIATOX-DF from March 2020 to February 2021, during the COVID-19 pandemic. At that time, there was an increase in accidental, environmental, venomous, and non-venomous animal cases, especially in babies, pre-adolescents, adolescents (11 to 15 years old), and women, due to the greater exposure of this age group and gender who have spent more time in rural environments. Most poisonings were accidental. It was observed that there was a decrease in suicide cases, but within these cases, there was a trend increase in poisoning in pre-adolescents and adolescents (11 to 15 years old) compared to other ages, which can be related to an increase in anxiety within this age group. The main toxic agents were venomous and non-venomous animals. The pattern of high frequency in cases involving medicines, pesticides, and household cleaning products was maintained, with a significant increase in cases involving 70% alcohol. It was found that patients living in towns further away from the Pilot Plan in Brasilia suffer accidents involving venomous animals. Accidental and attempted suicide cases occurred more frequently in cities closer to the Pilot Plan region. We concluded that these changes were explained by the new pattern of social behavior during the pandemic.